Photochemical transformation of antibiotics by excitation of Fe(III)-complexes in aqueous medium - Batista, Ana Paula S. [UNESP]; Cottrell, Barbara A.; Pupo Nogueira, Raquel F. [UNESP] (Elsevier B.V., 2014)
The degradation of sulfadiazine (STZ) and sulfathiazole (SDZ) induced by the excitation of ferric ions (Fe3+) was studied in this work. The effect of Fe3+ ion concentration, pH, iron complexation and irradiation source on the loss of these contaminants were evaluated. The increase of Fe3+ concentration from 0.20 to 0.60 mmol L-1 at pH 2.5 improved the generation of Fe2+ ions during irradiation of Fe(III)-aquacomplex achieving a maximum of 457 +/- 0.68 mu mol L-1 after 60min. However, the increase of pH from 2.5 to 4 decreased the concentration of Fe2+ to 169 +/- 0.59 mu mol L-1. The presence of Fe(III)-oxalate had a positive effect on antibiotics' degradation when compared to either Fe(III)-citrate or Fe(III)-aquacomplex complexes. Antibiotic degradation was improved during sunlight irradiation resulting in concentrations of both STZ and SDZ below the detection limit after an UV doses of 43 and 22J cm(-2) UV respectively (80 and 50 min) in the presence of Fe(III)-oxalate. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Sulfonamides; Iron complexation; Photolysis process; Blacklight irradiation; Sunlight irradiation